2021
DOI: 10.4081/jlimnol.2021.2007
|View full text |Cite
|
Sign up to set email alerts
|

Mercury methylation in oxic aquatic macro-environments: a review

Abstract: Mercury methylation in aquatic environments is a key process that incorporates this neurotoxin into the food chain and ultimately the human diet. Mercury methylation is considered to be essentially biotic and mainly driven by sulfate-reducing bacteria present in the bottom sediments in aquatic systems. However, in recent decades, many researchers have shown that this methylation also occurs in oxic layers in conjunction with a high content of particulate organic matter and localized depletion of dissolved oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 79 publications
1
16
0
Order By: Relevance
“…Moreover, k m measured in sinking particles of the oxic water column presented similar ranges as those reported from anoxic water bodies such as Canadian lakes (0.56-14.8⋅10 − 2 day − 1 ) (Eckley et al, 2005) and the Baltic Sea (1.6-4.8⋅10 − 3 day − 1 ) (Soerensen et al, 2018). Sinking particlesalso called settling particles or lacustrine/marine snowprovide microhabitats with anaerobic niches for microorganisms (Bianchi et al, 2018) and are thus suspected to be suitable habitats for Hg methylators (Gallorini and Loizeau, 2021; because this process happens in absence of oxygen (Bravo and Cosio, 2020). For instance, an experiment by Ortiz et al (2015) showed the potential of sinking particles to be adequate for Hg methylation by detecting significant k m in controlled microcosms.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, k m measured in sinking particles of the oxic water column presented similar ranges as those reported from anoxic water bodies such as Canadian lakes (0.56-14.8⋅10 − 2 day − 1 ) (Eckley et al, 2005) and the Baltic Sea (1.6-4.8⋅10 − 3 day − 1 ) (Soerensen et al, 2018). Sinking particlesalso called settling particles or lacustrine/marine snowprovide microhabitats with anaerobic niches for microorganisms (Bianchi et al, 2018) and are thus suspected to be suitable habitats for Hg methylators (Gallorini and Loizeau, 2021; because this process happens in absence of oxygen (Bravo and Cosio, 2020). For instance, an experiment by Ortiz et al (2015) showed the potential of sinking particles to be adequate for Hg methylation by detecting significant k m in controlled microcosms.…”
Section: Introductionsupporting
confidence: 75%
“…Although Hg methylation to form MeHg is a process known to occur in the absence of oxygen, the in-situ production of MeHg was often reported in oxic marine waters (Monperrus et al, 2007;Heimbürger et al, 2010;Lehnherr et al, 2011;Blum et al, 2013) and rarely in oxic lake water columns (Gascón Díez et al, 2016;Gallorini and Loizeau, 2021) which raises questions about the compartments where this process might occur. The understanding and quantification of the potential MeHg formation in oxic environments are crucial since it may significantly contribute to the overall budget of MeHg production in the environment (Gallorini and Loizeau, 2021), especially considering that oxygenated water bodies represent the vast majority of the total volume of water on Earth (Gnanadesikan et al, 2012). Such a question is of importance because of the need to understand the source and fate of Hg in the environment to predict how current environmental change and subsequent consequences, i.e., deoxygenation (Jane et al, 2021) will impact the formation of MeHg in our near-future ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in this small eutrophic lake, the epilimnetic pathway is likely of greater importance for MeHg bioaccumulation in the trophic web than the MeHg benthic-hypolimnetic pathway. Additionally, both pools appear to be largely disconnected, as suggested in a recent review by Gallorini and Loizeau (Gallorini and Loizeau, 2021).…”
Section: Thg and Mehg In Sediment Traps And The Upper Bottom Sediment...mentioning
confidence: 79%
“…The production of aquatic environments that simulate known freshwater and oceanic or marine environments with an arbitrarily high complexity of composition reproduction does not present significant technical problems at the moment -up to models that include microbiological components, fluid models for specific geographical locations, specific exposure levels -imitating the photochemistry and photohydrochemistry of mercury and the presence of specific dissolved or precipitated forms, etc. (Regnell and Watras, 2018;Zhu et al, 2018;Jinadasa and Fowler, 2019;Kimáková et al, 2019;Yan et al, 2019;Luo et al, 2020;Branfireun et al, 2020;Helmrich et al, 2021;Gallorini and Loizeau, 2021). Moreover, in the presence of modern models that reconstruct trends (which is a consequence of the analysis of "big data" about natural ecosystems), not only reconstruction is available for known environmental conditions, but also for arbitrary conditions for which a plausible calculation of the state in computational models is possible.…”
Section: Discussionmentioning
confidence: 99%